ANALYTICAL STUDY OF DURABILITY AND CONTACT CHARACTERISTICS OF METAL-POLYMER COMPOSITE SLIDING BEARINGS FOR MEANS OF TRANSPORT - Myron CHERNETS; Rafał WRONA; Yuriy CHERNETS (Scientific Journal of Silesian University of Technology. Series Transport)
The field of application of metal-polymer bearings is vast: transport of various types, processing industry equipment, medical equipment, various types of maintenance equipment, etc. With the use of the developed generalized author's analytical method of metal-polymer plain bearings on the basis of which it is laid the author's research methodology of materials wear kinetics at sliding friction (dry, lubricated), calculation of their durability is carried out. Contact parameters are also determined. Metal-polymer bearings with a bushing made of PA6, PA66 polyamide and PA6 based composites filled with glass (PA6 + 30GF) and carbon (PA6 + 30CF) dispersed fibres, molybdenum disulphide (PA6 + MoS2) and oil filled cast polyamide (PA6 + oil) are considered. These polyamides (unfilled and filled), as self-lubricating materials, are widely used in this type of dry friction sliding bearings. The predictive estimation of durability of investigated bearings depending on loading, polymer materials Young's modulus, their wear resistance and sliding friction coefficient is executed. Regularities of change from the specified factors of bearing's durability and the maximum contact pressures are established. Experimental indicators, diagrams, and wear resistance characteristics of the specified polymeric materials are presented. The results of researches of sliding friction coefficient and modulus of elasticity for carbon steel (0.45%C) – polyamides tribocouples are presented.